Carbon dioxide-based polyamide and preparation method and application thereof
Patent Information
- Application Number
- CN202611400704.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-10
- Publication Date
- 2026-10-13
AI Technical Summary
文献(Non-Isocyanate Polyurethanes from Carbonated Soybean Oil Using Monomeric orOligomeric Diamines To Achieve Thermosets or Thermoplastics[J].Macromolecules, 2016, 49(6): 2162-2171.)利用端氨基寡聚酰胺与碳酸酯化植物油的反应,同样证实了传统开环加成路径只能得到断裂伸长率为400%的无定形或交联态弹性体,无法获得高熔点工程塑料
[0013]第一,性能优势:通过缩聚机理的优化生成结构规整的聚脲或线性结构。所得材料具有高结晶度、低吸水率和优异的热稳定性,可熔融加工,是真正可进行熔融纺丝和注塑的工程塑料。
Smart Images

Figure CN122897989A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of polymer preparation, and relates to a carbon dioxide-based polyamide, its preparation method, and its application. Background Technology
[0002] Polyamide (PA) has become one of the most widely used thermoplastic engineering plastics at home and abroad due to its excellent comprehensive properties. It is also the world's second largest fiber material after polyester fiber, and is widely used in aerospace, machinery manufacturing, electronic information, chemical engineering, material packaging, sports and leisure and other fields.
[0003] The synthesis and application of existing carbon dioxide-based polymers mainly focus on two forms. One is the direct copolymerization with carbon dioxide to form polymers. For example, patent application CN116410455A discloses a method for preparing polyester by copolymerization of carbon dioxide and epoxide, which uses epoxy components to directly polymerize with gaseous carbon dioxide to form copolyester. However, the direct utilization of gaseous carbon dioxide requires harsh reaction conditions, making it difficult to achieve large-scale, efficient, and continuous production. The other is the preparation of polymers using carbon dioxide derivatives or further conversion materials (such as dimethyl carbonate, ethylene carbonate, etc.). For example, patent application CN119613683A discloses a method for synthesizing branched polyesters and its products using polyesters and carbon dioxide derivatives. Branched polyesters are prepared by transesterification reaction of carbon dioxide derivatives (such as 3-ethylidene-6-vinyltetrahydro-2H-pyran-2-one, etc.) with polyester materials under solid-phase conditions. Patent application CN113105600A discloses a silicate / isocyanate composite elastomer and its preparation method, which uses dimethyl carbonate converted from carbon dioxide as a raw material for the reaction. Currently reported polymers of carbon dioxide and its derivatives are mainly used in polyester and polyurethane materials, but no successful reports have been found in the field of polyamide, especially in high-performance engineering plastics.
[0004] It should be noted that while there are precedents for reacting carbon dioxide-based monomers with terminal amino prepolymers, existing technologies mainly employ ring-opening addition polymerization, i.e., the reaction of amines with cyclic carbonates to generate non-isocyanate polyurethanes (NIPUs). For example, patent application CN114891180A utilizes the reaction of terminal amino polysiloxanes with cyclic carbonates to prepare a self-healing polyurethane soft coating dependent on a side-group hydroxyl hydrogen bond network; patent application CN104650322A utilizes terminal amino polyurea oligomers for multifunctional chain extension to generate a thermosetting polyurea / epoxy hybrid crosslinking network that is difficult to melt process. The literature (Non-Isocyanate Polyurethanes from Carbonated Soybean Oil Using Monomeric or Oligomeric Diamines To Achieve Thermosets or Thermoplastics[J].Macromolecules, 2016, 49(6): 2162-2171.) also confirmed that the traditional ring-opening addition route can only obtain amorphous or cross-linked elastomers with an elongation at break of 400%, and cannot obtain high-melting-point engineering plastics by using the reaction of terminal amino oligomers with carbonated vegetable oil.
[0005] The fundamental reason for these limitations lies in the fact that the amine attack on the cyclic carbonate in the NIPU route leads to the inevitable residual side hydroxyl groups (-OH) in the product structure. Although these hydroxyl groups can form hydrogen bonds, they also result in high water absorption, low thermal stability, and extremely high difficulty in melt processing, typically limiting their application to thermosetting materials or coatings and failing to meet the requirements of engineering plastics. Furthermore, from the perspective of synthesis process and safety, the few studies attempting polycondensation routes either rely on the highly reactive but toxic diphenyl carbonate (DPC), producing phenolic byproducts; or, when using the green monomer dimethyl carbonate, its low reactivity, volatility, and susceptibility to methylation side reactions make it difficult to obtain high molecular weight products through direct polycondensation.
[0006] In summary, there is currently a lack of a method in the prior art that can effectively utilize carbon dioxide-based monomers to prepare high molecular weight, melt-processable, and crystalline carbon dioxide-based polyamides via a polycondensation route. Summary of the Invention
[0007] The purpose of this invention is to solve the above-mentioned problems in the prior art and to provide a carbon dioxide-based polyamide, its preparation method, and its application.
[0008] To achieve the above objectives, the technical solution adopted by the present invention is as follows:
[0009] A method for preparing carbon dioxide-based polyamide involves mixing a double-terminated amino polyamide prepolymer, a carbon dioxide-based monomer, and a reaction aid, followed by a polycondensation reaction to obtain the carbon dioxide-based polyamide.
[0010] The reaction aids include catalyst a, which is lithium acetylacetonate and / or carbonate;
[0011] Polycondensation reaction is divided into a pre-polymerization reaction stage and a final polymerization reaction stage. In the pre-polymerization reaction stage, condensation reflux is carried out during the reaction process, and the column top temperature of the condensation system is controlled to be lower than the boiling point of the carbon dioxide-based monomer.
[0012] This invention introduces carbon dioxide-based monomers through a melt polycondensation strategy of "double-terminated amino polyamide prepolymer + carbon dioxide-based monomer", which has the following advantages:
[0013] First, performance advantages: By optimizing the polycondensation mechanism, well-structured polyurea or linear structures are generated. The resulting material has high crystallinity, low water absorption, and excellent thermal stability. It can be melt-processed and is a true engineering plastic that can be melt-spun and injection-molded.
[0014] Second, the process advantages: By adopting the prepolymer method and combining the segmented process of atmospheric pressure pre-condensation and high vacuum final condensation with a specific catalytic system, the problems of easy volatility of carbon dioxide-based monomers and uncontrollable side reactions are effectively overcome, and high molecular weight polymers that are difficult to achieve by traditional methods are successfully prepared.
[0015] Third, environmental advantages: It abandons highly toxic phosgene and toxic phenol precursors, selects carbon dioxide-based monomers as raw materials, and uses methanol, ethanol or corresponding diols as by-products, thus achieving greening of raw material sources and production processes.
[0016] Existing technologies involve polycondensation reactions of diamino-terminated polyamide prepolymers with certain monomers, most typically diisocyanates, diepoxides, bisoxazolines, and diacids / diacid chlorides. However, replacing these monomers with carbon dioxide-based monomers is not readily conceived because such a replacement is not a simple equivalent substitution but involves a fundamental change in the reaction mechanism. For example, replacing highly reactive isocyanates with inert carbon dioxide-based monomers presents significant thermodynamic and kinetic obstacles. During the reaction of carbon dioxide-based monomers, to drive the reaction, the corresponding alcohol byproducts must be completely removed from the high-viscosity polymer melt. Even trace amounts of residual byproducts will cause the reaction to reverse, initiating degradation. In high-temperature melts, controlling the non-volatile nature of carbon dioxide-based monomers while simultaneously removing byproducts is extremely difficult thermodynamically. Furthermore, methyl-containing carbonate monomers undergo methylation at high temperatures (>180°C), a side reaction that permanently seals the terminal amino groups, rendering them inactive and leading to chain extension termination, thus preventing the acquisition of high molecular weight products.
[0017] To achieve the polycondensation reaction between the amino-terminated polyamide prepolymer and the carbon dioxide-based monomer, this invention first uses a highly efficient catalyst a (lithium acetylacetone and / or carbonate) to minimize the activation energy required for the reaction, thereby controlling the reaction temperature at a low level. Even so, some low-boiling-point carbon dioxide-based monomers, such as dimethyl carbonate, will still volatilize in large quantities. In order to continuously condense and reflux the carbon dioxide-based monomers and remove the corresponding alcohol byproducts from the system, condensation and reflux must be carried out simultaneously with pre-polymerization (at atmospheric pressure), and the column top temperature of the condensation system must be strictly controlled to be lower than the boiling point of the carbon dioxide-based monomers. In this way, only byproducts are continuously removed from the system. After the pre-polymerization is completed, final polymerization is carried out by applying a high vacuum. At this time, the carbon dioxide-based monomers have completely reacted, and there is no longer a need for a condensation and reflux device. Byproducts can be directly removed by continuously using the high vacuum.
[0018] As a preferred technical solution:
[0019] The carbon dioxide-based polyamide preparation method described above produces a prepolymer with a number-average molecular weight of 1000-5000 g / mol.
[0020] The preparation method of the carbon dioxide-based polyamide described above involves the following steps for preparing the bi-amino-terminated polyamide prepolymer: A lactam, a diamine, and deionized water are mixed and then subjected to a polymerization reaction; or, an amino acid, a diamine, and catalyst b are mixed and then subjected to a polymerization reaction to obtain the bi-amino-terminated polyamide prepolymer. The catalyst b is lithium acetylacetone and / or carbonate. The polymerization reaction pressure is 0.2-0.6 MPa, the temperature is 200-250 °C, and the time is 2-5 h.
[0021] The reaction conditions for the biamine-terminated polyamide prepolymer of this invention are mild, with a temperature (200-250°C) slightly lower than the industrial standard (260-270°C) and a pressure (0.2-0.6 MPa) in the low-to-medium pressure range. This is designed to keep water in the liquid / dense gas phase for catalytic ring-opening while preventing the diamine from volatilizing too quickly. Most existing technologies consider low molecular weight products as incompletely reacted products; however, this invention deliberately stops at the low molecular weight stage (1000-5000 g / mol).
[0022] This incomplete polymerization and specific process control have led to the following key technological advancements for subsequent reactions:
[0023] Firstly, there is an advancement in rheological matching. Subsequent reactions require the uniform dispersion of an extremely low-viscosity liquid (carbon dioxide-based monomer) into the polyamide melt. If existing high-molecular-weight PA6 (with extremely high melt viscosity) is used, the carbon dioxide-based monomer cannot effectively diffuse into the melt, and it will vaporize instantaneously due to localized overheating during mixing, leading to reaction failure. The low-molecular-weight prepolymer (1000-5000 g / mol) prepared in this invention has a much lower melt viscosity at 230°C, allowing for homogeneous mixing of the carbon dioxide-based monomer and ensuring efficient mass transfer in the subsequent chain extension reaction.
[0024] Secondly, there is an advancement in the concentration of highly reactive end groups: the reactivity of carbon dioxide-based monomers is much lower than that of isocyanates. In order to complete the reaction within a limited residence time, the reactant concentration must be increased according to kinetic principles. The high-concentration terminal amino fluid (low molecular weight prepolymer) prepared by the method of this invention compensates for the small reaction rate constant of carbon dioxide-based monomers, making non-isocyanate chain extension kinetically possible.
[0025] Finally, there is progress in suppressing diamine volatilization and stoichiometric control: by employing a pressure of 0.2-0.6 MPa and a relatively mild temperature (not exceeding 250°C), this method effectively suppresses the loss of volatile diamines. In conventional high-temperature, low-pressure processes (conventional high temperature is 260°C, and low pressure is 1 standard atmosphere), diamines easily volatilize with water vapor, leading to an imbalance in the end-group ratio. The method of this invention ensures a strict dual-terminal amino functionality of the prepolymer, which is crucial for subsequent linear chain extension with carbon dioxide-based monomers.
[0026] In summary, the difference in the prepolymer preparation method of this invention lies in the preparation of a prepolymer adapted to the specific reaction with the carbon dioxide-based monomer. It is not intended to manufacture the final material, but rather to create a highly reactive, low-viscosity, end-group-controlled reaction intermediate, thereby solving the engineering challenge of the difficulty in reacting carbon dioxide-based monomers in polymer melts.
[0027] Taking caprolactam as the lactam and hexamethylenediamine as the diamine as an example, the polymerization reaction equation is as follows:
[0028] .
[0029] In the preparation method of carbon dioxide-based polyamide as described above, the lactam is caprolactam or decanolactam, the amino acid is 11-aminoundecanoic acid, and the diamine is one or more of C4-C10 diamines; the molar ratio of lactam or amino acid to diamine is 6-40:1, the mass of deionized water added is 2-3% of the mass of lactam added, and the mass of catalyst b added is 100-800 ppm of the mass of amino acid added.
[0030] In the preparation method of carbon dioxide-based polyamide as described above, the carbon dioxide-based monomer is one or more of dimethyl carbonate, diethyl carbonate, ethylene carbonate, propylene carbonate, and methyl ethyl carbonate; the molar amount of the carbon dioxide-based monomer added is 1.1-2 times the molar amount of the diamine used to prepare the double-terminated amino polyamide prepolymer.
[0031] In the preparation method of carbon dioxide-based polyamide as described above, the carbonate is potassium carbonate or sodium carbonate; the mass of catalyst a added is 100-400 ppm of the mass of the double-terminated amino polyamide prepolymer.
[0032] In the preparation method of carbon dioxide-based polyamide as described above, the reaction aids also include antioxidants, which are one or more of antioxidant 1010, antioxidant 168 or antioxidant 616; the amount of antioxidant added is 100-500 ppm of the mass of the double-terminated amino polyamide prepolymer.
[0033] In the preparation method of carbon dioxide-based polyamide as described above, the pressure of the pre-condensation reaction stage is 1 standard atmosphere, the temperature is 200-230℃, and the time is 1-2 hours.
[0034] In the preparation method of carbon dioxide-based polyamide as described above, the pressure of the final polycondensation reaction stage is 100-300 Pa, the temperature is 240-270 °C, and the time is 3-5 h.
[0035] Taking the reaction of ethylene carbonate and diamine-terminated polyamide prepolymer as an example (the diamine-terminated polyamide prepolymer is prepared using caprolactam), the final polycondensation reaction is as follows:
[0036]
[0037] .
[0038] The present invention also provides a carbon dioxide-based polyamide, which is prepared by a method for preparing carbon dioxide-based polyamide as described in any of the preceding claims; the number average molecular weight of the carbon dioxide-based polyamide is 18,000-33,000 g / mol, the molecular weight distribution index is 1.5-3.0, and the melting point is 170-220℃.
[0039] The present invention also provides the application of carbon dioxide-based polyamide in the preparation of fibers, films or plastic products, wherein the carbon dioxide-based polyamide is one of the carbon dioxide-based polyamides described above.
[0040] Beneficial effects:
[0041] (1) The carbon dioxide-based polyamide of the present invention has a high molecular weight, with a number average molecular weight of 18,000-33,000 g / mol and a molecular weight distribution index of 1.5-3.0. It is also crystalline and has a melting point of 170-220°C. It can achieve stable melt processing in conventional injection molding or extrusion equipment, overcoming the shortcomings of the traditional NIPU route caused by side hydroxyl groups.
[0042] (2) The preparation method of the present invention uses carbon dioxide-based monomers as chain growth components. While ensuring that the polyamide chain length remains unchanged, the introduction of carbon dioxide-based monomers significantly reduces the dependence on fossil resources and realizes the preparation of low-carbon polyamides.
[0043] (3) The preparation method of the present invention does not require the use of phosgene or isocyanate. The lithium acetylacetonate and / or carbonate used are commercially available catalysts. Only condensation reflux and temperature control are required. After mixing, direct polycondensation is carried out without intermediate separation. The process is simple and can be prepared on a large scale in existing polymerization equipment. It has high production efficiency, low cost and great application prospects.
[0044] (4) The preparation method of the present invention has a wide range of applications. By selecting terminal amino polyamide prepolymers with different structures (such as oligomers such as PA6, PA11, PA10, etc.) and reacting them with carbon dioxide-based monomers, a series of carbon dioxide-based copolyamides can be flexibly prepared. Attached Figure Description
[0045] Figure 1 This is the 1H NMR spectrum of the carbon dioxide-based polyamide prepared in Example 1 of this invention (where n=8, x=17).
[0046] Figure 2 This is the Fourier transform infrared spectrum (KBr tablet method) of the carbon dioxide-based polyamide prepared in Example 1 of this invention.
[0047] Figure 3 This is the 1H NMR spectrum of the carbon dioxide-based polyamide prepared in Example 2 of this invention;
[0048] Figure 4 This is the Fourier transform infrared spectrum (KBr tablet method) of the carbon dioxide-based polyamide prepared in Example 2 of this invention.
[0049] Figure 5 This is the Fourier transform infrared spectrum (KBr tablet) of the carbon dioxide-based polyamide prepared in Example 3 of this invention.
[0050] Figure 6 This is the Fourier transform infrared spectrum (KBr tablet) of the carbon dioxide-based polyamide prepared in Example 4 of this invention. Detailed Implementation
[0051] The present invention will be further described below with reference to specific embodiments. It should be understood that these embodiments are for illustrative purposes only and are not intended to limit the scope of the invention. Furthermore, it should be understood that after reading the teachings of this invention, those skilled in the art can make various alterations or modifications to the invention, and these equivalent forms also fall within the scope defined by the appended claims.
[0052] The following are the relevant performance testing methods for each embodiment and comparative example:
[0053] (1) Number-average molecular weight of the diamino-terminated polyamide prepolymer: Since the number-average molecular weight of the diamino-terminated polyamide prepolymer in the system of this invention is 1000-5000 g / mol, which is in the lower oligomer range, the resolution of traditional gel permeation chromatography in this range is insufficient. Therefore, this invention uses chemical end-group titration to determine its number-average molecular weight. The specific detection method is as follows: First, accurately weigh about 1.0000 g of vacuum-dried diamino-terminated polyamide prepolymer powder sample on a balance of 0.001 g and place it in a stoppered conical flask; then, add 50 mL of a mixed solvent prepared by m-cresol and isopropanol in a volume ratio of 8:2, place it on a heated magnetic stirrer, and slowly heat it at ≤80°C until the sample is completely dissolved to form a uniform viscous solution; finally, after the solution cools to 25°C, insert a calibrated composite glass electrode and use a Metrohm 905 electrode. The Titrando fully automated potentiometric titrator performs potentiometric titration using a p-toluenesulfonic acid-methanol standard titration solution precisely calibrated to 0.0500 mol / L. The instrument is set to record the volume of standard solution consumed at the potential jump point (i.e., the equivalence point). The concentration of terminal amino groups (mmol / g) per unit mass of the diamino-terminated polyamide prepolymer is calculated from the consumed volume, and the number-average molecular weight is then calculated using the following formula:
[0054] terminal amino concentration (Unit: mmol / g):
[0055] ;
[0056] In the formula:
[0057] V represents the volume of standard titration solution consumed in titrating the sample, in mL;
[0058] V0 is the volume of standard titration solution consumed in the titration of blank solvent, in mL;
[0059] C represents the concentration of the p-toluenesulfonic acid-methanol standard titration solution, in mol / L.
[0060] m represents the mass of the amino-terminated polyamide prepolymer sample, in grams.
[0061] Based on its functionality of 2 (i.e., each molecular chain contains two terminal amino groups), calculate the number-average molecular weight Mn (unit: g / mol):
[0062] .
[0063] (2) Number average molecular weight and molecular weight distribution index of carbon dioxide-based polyamide: The results were obtained in accordance with the national standard GB / T36214.1-2018 "Determination of average molecular weight and molecular weight distribution of polymers by volume exclusion chromatography - Part 1: General method".
[0064] The following specific conditions are stipulated for standard implementation: The test is conducted using a gel permeation chromatography system (Waters Alliance e2695 system) equipped with a differential refractive index detector (RI). The mobile phase must be hexafluoroisopropanol (HFIP), with 0.05 mol / L potassium trifluoroacetate added as a salt inhibitor to suppress polymer chain aggregation and non-ideal interactions with the column packing material. During the test, the column oven temperature is maintained at a constant 40°C to reduce solvent viscosity, and the mobile phase flow rate is set to 1.0 mL / min. The sample must be pre-prepared to a concentration of 2.0 mg / mL, filtered through a 0.22 μm polytetrafluoroethylene (PTFE) filter before injection. A calibration curve is established using polymethyl methacrylate (PMMA) standard samples as a reference. After the test, the curve is integrated to calculate the weight-average molecular weight (Mw), number-average molecular weight (Mn), and molecular weight distribution index (PDI) = Mw / Mn.
[0065] (3) Melting point of carbon dioxide-based polyamide: The melting point was determined in accordance with the provisions of GB / T 19466.3-2004 "Differential scanning calorimetry (DSC) for plastics - Part 3: Determination of melting and crystallization temperature and enthalpy".
[0066] The testing equipment used was a Mettler Toledo DSC 3+ differential scanning calorimeter. For sample preparation, 5.0-10.0 mg of polyamide sample was weighed using a balance, placed in a standard aluminum crucible, and pressed firmly. The entire test was conducted under continuous purging with high-purity nitrogen (≥99.999% purity) at a flow rate of 50 mL / min to prevent oxidative degradation of the polymer at high temperatures, which would affect the heat flux signal. The test procedure was as follows: the sample was heated from room temperature to 250°C at a constant heating rate of 10°C / min and held at this temperature for 3 minutes; then cooled to 50°C at a cooling rate of 10°C / min and held at this temperature for 3 minutes; finally, the temperature was increased again to 250°C at a rate of 10°C / min. The melting point (melting temperature) of the product was obtained by integrating the second heating curve.
[0067] (4) Tensile strength of fibers: Fiber performance testing was conducted according to the national standard GB / T 14337-2022 "Test Method for Tensile Properties of Short Chemical Fibers". Fiber samples must be placed in a standard atmospheric environment with a temperature of (20±2)℃ and a relative humidity of (65±5)% for 24 hours before testing to eliminate the influence of moisture on the plasticizing effect of polyamide. An Instron 3365 monofilament tensile strength testing machine was used as the testing instrument. During testing, the initial nominal spacing of the clamps was set to 10mm or 20mm (20mm for nominal fiber length ≥ 35mm; 10mm for nominal fiber length < 35mm), and the tensile test speed was set to 20mm / min. A corresponding pre-tension was applied according to the linear density of a single fiber to straighten the fiber without causing tensile deformation, ultimately obtaining the fiber's tensile strength (cN).
[0068] (5) Tensile yield stress of film: The test was conducted in accordance with the national standard GB / T 1040.3-2006 "Determination of tensile properties of plastics - Part 3: Test conditions for films and sheets". Specifically, a type 5 dumbbell-shaped specimen (total specimen length 75 mm, gauge length 25 mm, narrow part width 6 mm) was used. The specimen thickness was the arithmetic mean of the thickness measured at 5 points evenly distributed within the gauge length. Five parallel specimens were prepared for each group, and the test was conducted along the longitudinal direction (MD) and transverse direction (TD) respectively. Before the test, the specimens were placed in a standard environment with a temperature of 23±2℃ and a relative humidity of 50%±5% for 48 hours. The test was conducted using an Instron 3365 universal testing machine equipped with pneumatic clamps with anti-slip pads. The test speed was set to 50 mm / min, and the initial distance between the upper and lower clamps was 50 mm. During the test, the tensile stress-strain curve was recorded, and the stress value corresponding to the yield point was read from the curve, which is the tensile yield stress (MPa) of the film. For materials exhibiting a clear yield point, the peak stress is taken; for materials without a clear yield point, the stress value at 2% strain is taken. The arithmetic mean of five parallel specimens is taken as the final test result of the tensile yield stress of the film.
[0069] (6) Notched impact strength of plastic products: The test will be conducted in accordance with the national standard GB / T 1043.1-2008 "Determination of impact performance of simply supported plastic beams - Part 1: Non-instrumental impact test". The specimen is processed into a cuboid with a length of 80 mm, a width of 10 mm, and a height of 4 mm using a standard injection mold, and an A-type notch is processed in the middle position using a notch sample preparation machine (the radius of curvature at the bottom of the notch is strictly controlled to be 0.25 mm). Before the test, the specimen needs to be conditioned for 16 hours in an environment of 23±2℃ and relative humidity of 50±5%. On the impact testing machine, the span between the two supports of the specimen is set to 62 mm, and the fracture absorption energy is ensured to fall within the range of 10%~80% of the rated energy of the pendulum. The impact velocity is 2.9 m / s, and then a 2J pendulum is used to impact and break the specimen. The notched impact strength (kJ / m²) of the plastic product is then calculated. The arithmetic mean of 5 parallel specimens is taken as the final test result of the notched impact strength of the plastic product.
[0070] Example 1
[0071] A method for preparing carbon dioxide-based polyamide, the specific steps of which are as follows:
[0072] (1) Raw material preparation
[0073] Caprolactam;
[0074] Diamine: 1,6-hexanediamine;
[0075] Deionized water;
[0076] Nitrogen;
[0077] Carbon dioxide-based monomer: ethylene carbonate, boiling point 248℃;
[0078] Antioxidant: Antioxidant 1010, manufactured by BASF, brand name Irganox 1010;
[0079] Catalyst a: Sodium carbonate;
[0080] (2) Preparation of amino-terminated polyamide prepolymers
[0081] Caprolactam, diamine, and deionized water were mixed and then subjected to a polymerization reaction. The polymerization reaction was carried out at a pressure of 0.2 MPa, a temperature of 200 °C, and a time of 2 h. The molar ratio of caprolactam to diamine was 6:1, and the amount of deionized water added was 2% of the mass of caprolactam.
[0082] After the polymerization reaction is completed, the reaction system is depressurized to 1 standard atmosphere at a rate of 0.01 MPa / min. Then, under nitrogen protection, the reaction product is squeezed out from the bottom valve of the reactor, quenched in a 25°C cold water bath and pelletized. Then, it is placed in a vacuum oven at a pressure of 100 Pa and a temperature of 50°C for 8 hours to obtain the double-terminated amino polyamide prepolymer.
[0083] The number-average molecular weight of the amino-terminated polyamide prepolymer is 1050 g / mol;
[0084] (3) Pre-condensation reaction
[0085] After mixing carbon dioxide-based monomers, antioxidants, catalyst a and all the double-terminated amino polyamide prepolymers obtained in step (2), a pre-condensation reaction was carried out. During the reaction, reflux was carried out and the column top temperature of the condensation system was controlled to be 230°C, which is lower than the boiling point of the carbon dioxide-based monomer.
[0086] The pre-condensation reaction was carried out at a pressure of 1 standard atmosphere, a temperature of 200℃, and a time of 1 hour.
[0087] The molar amount of carbon dioxide-based monomer added is 1.1 times the molar amount of diamine added to prepare the amino-terminated polyamide prepolymer;
[0088] The mass of catalyst a added is 100 ppm of the mass of the amino-terminated polyamide prepolymer;
[0089] The amount of antioxidant added is 100 ppm of the mass of the amino-terminated polyamide prepolymer;
[0090] (4) Final condensation reaction
[0091] After the pre-polymerization reaction was completed, the reaction system was subjected to a final polymerization reaction. The pressure of the final polymerization reaction was 300 Pa, the temperature was 240 °C, and the time was 3 h.
[0092] After the final polycondensation reaction is completed, the system is restored to 1 standard atmosphere, and the reaction product is squeezed out from the bottom valve of the reactor under nitrogen protection. After being cooled in a water bath at 25°C, stretched into strips, and granulated, it is placed in a vacuum oven at 100 Pa and 80°C for 24 hours to dry, thus obtaining carbon dioxide-based polyamide with a number average molecular weight of 18,500 g / mol, a molecular weight distribution index of 2.8, and a melting point of 172°C.
[0093] like Figure 1As shown, peak 6 in the 1H NMR spectrum of carbon dioxide-based polyamide indicates the formation of urethane bonds, confirming the successful introduction of carbon dioxide-based monomers in the final polycondensation stage; peaks 1' and 5 indicate the formation of amide bonds, confirming the successful preparation of the double-terminated amino polyamide prepolymer; the peaks at 1.5~2.0 ppm confirm that the carbon dioxide-based polyamide molecular chain has a large number of repeating units.
[0094] like Figure 2 As shown, peak 1 in the Fourier transform infrared spectrum of carbon dioxide-based polyamide is attributed to the NH stretching vibration of the urethane and amide groups under hydrogen bonding; peak 2 is attributed to the Fermi resonance between the NH stretching vibration of the urethane and amide groups and the overtone of the amide II band; peaks 3 and 4 are attributed to the asymmetric and symmetric stretching vibrations of -CH2-, respectively; peak 5 is attributed to the C=O stretching vibration of the urethane and amide groups; and peak 6 is attributed to the coupling of the NH bending vibration and the CN stretching vibration of the urethane and amide groups.
[0095] An application of carbon dioxide-based polyamide is described, in which the carbon dioxide-based polyamide prepared in this embodiment is used to prepare fibers. The specific steps are as follows: the carbon dioxide-based polyamide is stably melted at 250°C using a single-screw extruder, and extruded through a standard spinneret with an aperture of 0.25 mm under a spinning pressure of 15 MPa. After extrusion, the fibers are rapidly cooled and solidified by side-blown air at a speed of 0.5 m / s and a temperature of 20°C, with an air section length of 120 cm. Subsequently, the fibers are drawn through two stages of drawing rollers, with a total draw ratio of 3.5 times (of which the first stage draw ratio is 2.5 times and the second stage is 1.4 times). The temperature of the first drawing roller is 70°C and the temperature of the second drawing roller is 130°C. Finally, the fibers are wound into shape.
[0096] The prepared fiber has a specification of 1.63 dtex × 38 mm and a breaking strength of 5.7 cN, which meets the basic requirements for fiber strength of conventional textiles (such as clothing and home textiles).
[0097] Comparative Example 1
[0098] A method for preparing carbon dioxide-based polyamide differs from Example 1 only in that catalyst a is replaced with tetrabutyl titanate.
[0099] The prepared carbon dioxide-based polyamide had a number-average molecular weight of 9500 g / mol, a molecular weight distribution index of 3.8, and a melting point of 160℃.
[0100] One application of carbon dioxide-based polyamide is the preparation of fibers using the carbon dioxide-based polyamide of this comparative example, with the same steps as in Example 1. The tensile strength of the resulting fibers is only 2.1 cN.
[0101] Compared to Example 1, the number-average molecular weight of the carbon dioxide-based polyamide in Comparative Example 1 decreased, the molecular weight distribution index increased, and the melting point of the product also decreased to 160°C. This is because, in the high-temperature melt, a large number of terminal amino groups rapidly underwent extremely strong and almost irreversible complexation coordination with tetrabutyl titanate. This strong complexation significantly reduced the electron cloud density around the amino nitrogen atom, fundamentally weakening its ability as a nucleophile to attack the carbonyl carbon of ethylene carbonate, thus reducing the number-average molecular weight. Due to the loss of nucleophilic activity, the polycondensation reaction between the carbon dioxide-based monomer and the terminal amino groups was almost impossible under the same conditions. Moreover, the high temperature and strong complexation environment also led to side reactions such as decarboxylation of the carbon dioxide-based monomer, resulting in the deactivation and passivation of a large number of terminal amino groups due to complexation, a sharp decrease in the concentration of active chain ends, and premature termination of the molecular chain due to ineffective chain extension, thus increasing the molecular weight distribution index. In addition, due to the combined effect of the decrease in number-average molecular weight and the broadening of the molecular weight distribution, the melting point of the product also decreased.
[0102] Compared to Example 1, the breaking strength of the fiber in Comparative Example 1 was reduced. This is because the molecular weight of Comparative Example 1 is much lower than that of Example 1, which is capable of effective chain entanglement (18500 g / mol). When subjected to tensile stress, its melt-spun fiber cannot disperse stress through slippage and entanglement between molecular chains, resulting in rapid propagation of microcracks and macroscopic fracture, ultimately manifesting as an extreme decrease in fiber breaking strength.
[0103] This indicates that the sodium carbonate catalyst a of the present invention can promote urethane polycondensation in a mild and efficient manner, avoiding the poisoning effect of transition metals on the end groups, and is a key technical means to obtain high molecular weight, high strength fibers.
[0104] Comparative Example 2
[0105] A method for preparing carbon dioxide-based polyamide differs from Example 1 only in that catalyst a is replaced with zinc acetate.
[0106] The prepared carbon dioxide-based polyamide had a number-average molecular weight of 12,000 g / mol, a molecular weight distribution index of 3.2, and a melting point of 165 °C.
[0107] One application of carbon dioxide-based polyamide is the preparation of fibers using the carbon dioxide-based polyamide of this comparative example, with the same steps as in Example 1. The tensile strength of the resulting fibers is only 1.9 cN.
[0108] Compared to Example 1, the number-average molecular weight of the carbon dioxide-based polyamide in Comparative Example 2 decreased, the molecular weight distribution index increased, and the melting point of the product also decreased to 165°C. This is because zinc acetate lacks efficient coordination activation or proton transfer capabilities in the polymer melt, and cannot effectively lower the activation energy barrier of the polycondensation reaction. In this system lacking effective catalytic kinetics, the reaction between the ethylene carbonate monomer and the terminal amino group is severely kinetically retarded. The polycondensation reaction proceeds extremely slowly. Within the given pre- and final polycondensation time periods, the conversion rate (p) of the reactive groups cannot approach the limit value required for preparing the polymer (usually p > 0.99), thus significantly reducing the number-average molecular weight. Simultaneously, due to the extremely uneven reaction rate, some chain ends preferentially react and grow, while others remain unreacted, resulting in a severely uneven chain length distribution, thus significantly increasing the molecular weight distribution index. Furthermore, under harsh high-temperature reaction conditions, ethylene carbonate that does not participate in polycondensation in time is prone to decarboxylation decomposition side reactions, generating carbon dioxide and ethylene oxide derivatives. These byproducts will further undergo uncontrollable addition or cross-linking reactions with terminal amino groups, consuming active end groups and introducing irregular chain structures, further exacerbating the reduction in molecular weight and the broadening of the distribution, ultimately causing the melting point of the product to drop to 165℃.
[0109] Compared to Example 1, the tensile strength of the fibers in Comparative Example 2 was reduced. This is because the short and widely distributed molecular chains in the product could not form an effective macromolecular orientation hardening effect and physical entanglement network during melt spinning and under external tensile stress, resulting in a significant reduction in the tensile strength of the macroscopic fibers, which was only 1.9 cN.
[0110] Example 2
[0111] A method for preparing carbon dioxide-based polyamide, the specific steps of which are as follows:
[0112] (1) Raw material preparation
[0113] Decanolactam;
[0114] Diamine: 1,10-decanediamine;
[0115] Deionized water;
[0116] Nitrogen;
[0117] Carbon dioxide-based monomer: dimethyl carbonate, boiling point 90℃;
[0118] Antioxidant: Antioxidant 168, manufactured by BASF, brand name Irgafos 168;
[0119] Catalyst a: Potassium carbonate;
[0120] (2) Preparation of amino-terminated polyamide prepolymers
[0121] Decanolactam, diamine, and deionized water were mixed and then subjected to a polymerization reaction. The polymerization reaction was carried out at a pressure of 0.4 MPa, a temperature of 225 °C, and a time of 3.5 h. The molar ratio of decanolactam to diamine was 15:1, and the amount of deionized water added was 2.5% of the mass of decanolactam.
[0122] After the polymerization reaction is completed, the reaction system is depressurized to 1 standard atmosphere at a rate of 0.01 MPa / min. The reaction product is then extruded under nitrogen protection, quenched in a 25°C cold water bath and pelletized. Then it is placed in a vacuum oven at 100 Pa and 50°C for 8 hours to dry, thus obtaining the double-terminated amino polyamide prepolymer.
[0123] The number-average molecular weight of the amino-terminated polyamide prepolymer is 2300 g / mol;
[0124] (3) Pre-condensation reaction
[0125] After mixing carbon dioxide-based monomers, antioxidants, catalyst a and all the double-terminated amino polyamide prepolymers obtained in step (2), a pre-condensation reaction was carried out. During the reaction, reflux was carried out and the column top temperature of the condensation system was controlled to be 85°C, which is lower than the boiling point of the carbon dioxide-based monomer.
[0126] The pre-condensation reaction was carried out at a pressure of 1 standard atmosphere, a temperature of 215℃, and a time of 1.5 hours.
[0127] The molar amount of carbon dioxide-based monomer added is 1.5 times the molar amount of diamine added to prepare the amino-terminated polyamide prepolymer;
[0128] The mass of catalyst a added is 250 ppm of the mass of the amino-terminated polyamide prepolymer;
[0129] The amount of antioxidant added is 250 ppm of the mass of the amino-terminated polyamide prepolymer;
[0130] (4) Final condensation reaction
[0131] After the pre-polymerization reaction was completed, the reaction system was subjected to a final polymerization reaction. The pressure of the final polymerization reaction was 200 Pa, the temperature was 255 °C, and the time was 4 h.
[0132] After the final polycondensation reaction is completed, the system is restored to 1 standard atmosphere, and the reaction product is extruded from the bottom valve of the reactor under nitrogen protection. After being cooled in a water bath at 25°C, stretched into strips, and granulated, it is placed in a vacuum oven at 100 Pa and 80°C for 24 hours to dry, thus obtaining carbon dioxide-based polyamide with a number average molecular weight of 24600 g / mol, a molecular weight distribution index of 2.2, and a melting point of 188°C.
[0133] like Figure 3 As shown, peak 2 in the 1H NMR spectrum of carbon dioxide-based polyamide indicates the formation of urea bonds, confirming the successful introduction of carbon dioxide-based monomers in the final polycondensation stage; peaks 1 and 3 indicate the formation of amide bonds in the carbon dioxide-based polyamide product, confirming the successful preparation of the double-terminated amino polyamide prepolymer; the peaks at 1.5~2.3 ppm confirm that the carbon dioxide-based polyamide product molecular chain has a large number of repeating units.
[0134] like Figure 4 As shown, peaks 1 and 2 in the Fourier transform infrared spectrum of the carbon dioxide-based polyamide represent the coupling of the NH stretching vibration and NH bending vibration with the CN stretching vibration in the urea and amide bonds, respectively; peaks 3 and 4 represent the asymmetric and symmetric stretching vibrations of -CH2-, respectively; peak 5 represents the stretching vibration of C=O in the urea and amide bonds; and peak 6 represents the bending vibration of NH. Compared to the stretching vibrations of free -NH and -C=O, the stretching vibration peaks of these two chemical bonds in the carbon dioxide-based polyamide show a significant red shift, which is due to the formation of numerous hydrogen bonds between the functional groups in the carbon dioxide-based polyamide.
[0135] An application of carbon dioxide-based polyamide involves using the carbon dioxide-based polyamide prepared in this embodiment to prepare a film. The specific steps are as follows: the carbon dioxide-based polyamide is dried at 80°C for 24 hours in a dryer, then melted at 260°C in a single-screw extruder, and then evenly spread into a film through a T-die under a die head pressure of 6MPa. The molten film is then rapidly cooled and formed by contacting a cooling roller with a constant surface temperature of 40°C. The film thickness is controlled at 50μm.
[0136] The prepared film has a tensile yield stress of 46 MPa, which meets the conventional requirements for tensile strength of film substrates in food packaging, industrial tapes, electronic protective films, and agricultural films.
[0137] Comparative Example 3
[0138] A method for preparing carbon dioxide-based polyamide differs from Example 2 only in that the column top temperature of the condensation system is 90°C, which is equal to the boiling point of the carbon dioxide-based monomer.
[0139] The prepared carbon dioxide-based polyamide had a number-average molecular weight of 7500 g / mol, a molecular weight distribution index of 3.5, and a melting point of 158 °C.
[0140] One application of carbon dioxide-based polyamide is to use the carbon dioxide-based polyamide of this comparative example to prepare a film, with the same steps as in Example 2, and the tensile yield stress of the film obtained is only 15 MPa.
[0141] Compared to Example 2, the number-average molecular weight of the carbon dioxide-based polyamide in Comparative Example 3 decreased, the molecular weight distribution index increased, and the melting point of the product decreased. This is because: when the column top temperature was set to 90°C, which is the same as the monomer boiling point, dimethyl carbonate was in a boiling vaporized state, and the reflux effect was severely insufficient. A large amount of gaseous dimethyl carbonate and methanol byproducts continuously escaped from the reaction system, disrupting the stoichiometric ratio in the reactor. The polycondensation reaction requires a suitable molar ratio between terminal amino groups and carbonate groups. The large loss of dimethyl carbonate resulted in a much higher concentration of terminal amino groups in the remaining melt than that of carbonate groups. The reaction chain lacking coupling groups was terminated prematurely, thus reducing the number-average molecular weight. At the same time, due to the continuous and uneven decay of monomer concentration during the reaction, the reaction environment of different chain ends varied greatly. Some chain segments grew due to preferential coupling, while others stagnated due to monomer scarcity, resulting in a severely uneven chain length distribution, thus increasing the molecular weight distribution index. Finally, due to the combined effect of the decrease in number-average molecular weight and the widening of the molecular weight distribution, the melting point of the product also decreased.
[0142] Compared to Example 2, the tensile yield stress of the film in Comparative Example 3 was reduced. This is because when the column top temperature of the condensation system equals the boiling point of dimethyl carbonate, some dimethyl carbonate escapes from the reaction system along with methanol byproducts, causing a shift in the stoichiometric relationship between the carbonate groups and the terminal amino groups. This prevents the carbonylation chain extension reaction between the diamino-terminated polyamide prepolymers from proceeding sufficiently. Therefore, the number-average molecular weight of the product in Comparative Example 3 is only 7500 g / mol, and the molecular weight distribution index increases to 3.5, indicating that the system contains more low-molecular-weight segments and insufficiently extended prepolymers. Shorter molecular chains are less likely to form a stable and continuous chain entanglement network, and wider molecular chains also lead to uneven load-bearing capacity in different regions. At the same time, the number and uneven distribution of the urethane group linkages formed by dimethyl carbonate reduce the continuity of interchain hydrogen bonding and cohesion. When the film is stretched, the external stress is difficult to be uniformly transmitted between the molecular chains and crystal regions. Short chains are more likely to slip, and local stress concentration and microcracks are generated in the low molecular weight enrichment area. As a result, the film yields or fails under low stress, and the tensile yield stress is significantly lower than that in Example 2.
[0143] Comparative Example 4
[0144] A method for preparing carbon dioxide-based polyamide differs from Example 2 only in that the column top temperature of the condensation system is 110°C, which is higher than the boiling point of the carbon dioxide-based monomer.
[0145] The number-average molecular weight of the carbon dioxide-based polyamide was 3200 g / mol. Due to its extremely chaotic molecular structure, it was not practical to accurately determine its molecular weight distribution, and it was also impossible to detect a clear melting point in standard tests. The product was a viscous and brittle waxy solid.
[0146] Because the material lost its basic cohesive force and melt strength, attempts to prepare a film using the method of Example 2 and a fiber using the method of Example 1 both failed, with the tensile yield stress of the film and the breaking strength of the fiber both being 0.
[0147] Compared to Example 2, the number-average molecular weight of the carbon dioxide-based polyamide in Comparative Example 4 was significantly reduced, making it impossible to accurately determine the molecular weight distribution or detect a definite melting point. This is because when the column top temperature was set to 110°C, which is higher than the boiling point of dimethyl carbonate, during the prepolymerization stage, as the temperature inside the reactor increased, a large amount of dimethyl carbonate dissolved in the low molecular weight, low viscosity, dual-amino-terminated polyamide prepolymer melt underwent extremely violent flash evaporation, escaping completely within a few minutes, leaving only the highly thermally stable dual-amino-terminated polyamide prepolymer in the reactor. These prepolymers all have basic amino groups at their end groups, lacking the chemical basis for homopolymerization. Therefore, the molecular chains cannot effectively extend and grow, resulting in a significant decrease in number-average molecular weight. Simultaneously, since the monomers completely escape in the early stages of the reaction, there are no coupling groups in the system, preventing coupling reactions between the chain ends and causing a sharp widening of the molecular weight distribution index. During the subsequent hours of high-temperature operation, the polymer chains not only failed to grow but also broke further due to prolonged thermal degradation, severely damaging the chain structure and making it impossible to detect a definite melting point. Ultimately, because the molecular weight stagnates in the waxy region of ultra-oligopolymers, the intermolecular van der Waals forces and physical entanglement are almost zero, and the product loses basic cohesive strength and melt strength, making it impossible to process into films or fibers. The tensile yield stress and tensile strength are both zero.
[0148] Example 3
[0149] A method for preparing carbon dioxide-based polyamide, the specific steps of which are as follows:
[0150] (1) Raw material preparation
[0151] 11-Aminoundecanoic acid;
[0152] Diamine: 1,8-Octandiamine;
[0153] Nitrogen;
[0154] Carbon dioxide-based monomer: diethyl carbonate, boiling point 126℃;
[0155] Antioxidant: Antioxidant 616, manufactured by Beijing Jiyi Chemical Co., Ltd., brand name JY-616;
[0156] Catalyst a, catalyst b: lithium acetylacetonate;
[0157] (2) Preparation of amino-terminated polyamide prepolymers
[0158] 11-Aminoundecanoic acid, diamine, and catalyst b were mixed and then subjected to a polymerization reaction. The polymerization reaction was carried out at a pressure of 0.5 MPa, a temperature of 240 °C, and a time of 4.5 h. The molar ratio of 11-aminoundecanoic acid to diamine was 25:1, and the mass of catalyst b added was 400 ppm of the mass of 11-aminoundecanoic acid.
[0159] After the polymerization reaction is completed, the reaction system is depressurized to 1 standard atmosphere at a rate of 0.01 MPa / min. The reaction product is then extruded under nitrogen protection, quenched in a 25°C cold water bath and pelletized. Then it is placed in a vacuum oven at 100 Pa and 50°C for 8 hours to dry, thus obtaining the double-terminated amino polyamide prepolymer.
[0160] The number-average molecular weight of the amino-terminated polyamide prepolymer is 3800 g / mol;
[0161] (3) Pre-condensation reaction
[0162] After mixing carbon dioxide-based monomers, antioxidants, catalyst a and all the double-terminated amino polyamide prepolymers obtained in step (2), a pre-condensation reaction was carried out. During the reaction, reflux was carried out and the column top temperature of the condensation system was controlled to be 110°C, which is lower than the boiling point of the carbon dioxide-based monomer.
[0163] The pre-condensation reaction was carried out at a pressure of 1 standard atmosphere, a temperature of 225°C, and a time of 1.5 hours.
[0164] The molar amount of carbon dioxide-based monomer added is 1.8 times the molar amount of diamine added to prepare the amino-terminated polyamide prepolymer;
[0165] The mass of catalyst a added is 300 ppm of the mass of the amino-terminated polyamide prepolymer;
[0166] The amount of antioxidant added is 300 ppm of the mass of the amino-terminated polyamide prepolymer;
[0167] (4) Final condensation reaction
[0168] After the pre-polymerization reaction was completed, the reaction system was subjected to a final polymerization reaction. The pressure of the final polymerization reaction was 150 Pa, the temperature was 260 °C, and the time was 4 h.
[0169] After the final polycondensation reaction is completed, the system is restored to 1 standard atmosphere, and the reaction product is squeezed out from the bottom valve of the reactor under nitrogen protection. After being cooled in a water bath at 25°C, stretched into strips, and granulated, it is placed in a vacuum oven at 100 Pa and 80°C for 24 hours to dry, thus obtaining carbon dioxide-based polyamide with a number average molecular weight of 29,800 g / mol, a molecular weight distribution index of 1.9, and a melting point of 205°C.
[0170] like Figure 5 As shown, peaks 1 and 2 in the Fourier transform infrared spectrum of the carbon dioxide-based polyamide represent the coupling of the NH stretching vibration and NH bending vibration with the CN stretching vibration in the urethane and amide bonds, respectively; peaks 3 and 4 represent the asymmetric and symmetric stretching vibrations of -CH2-, respectively; peak 5 represents the stretching vibration of C=O in the urea and amide bonds; and peak 6 represents the bending vibration of NH. Compared to the stretching vibrations of free -NH and -C=O, the stretching vibration peaks of these two chemical bonds in the carbon dioxide-based polyamide show a significant red shift, which is due to the formation of numerous hydrogen bonds between the functional groups in the carbon dioxide-based polyamide.
[0171] An application of carbon dioxide-based polyamide: The carbon dioxide-based polyamide prepared in this embodiment is used to prepare plastic products. The specific steps are as follows: the carbon dioxide-based polyamide is melted at 265°C using a precision injection molding machine, and then filled into a cold mold of a standard notched impact specimen (mold temperature 80°C) under an injection pressure of 80MPa. The holding pressure is 60MPa, and the product is solidified and formed after a holding and cooling process of up to 10 seconds (of which the holding time is 4 seconds and the cooling time is 6 seconds).
[0172] The notched impact strength of the resulting plastic product is 6.2 kJ / m. 2 It meets the requirements of conventional fields such as automobiles, electronics, and packaging.
[0173] Example 4
[0174] A method for preparing carbon dioxide-based polyamide, the specific steps of which are as follows:
[0175] (1) Raw material preparation
[0176] Caprolactam;
[0177] Diamine: 1,4-Butanediamine;
[0178] Deionized water;
[0179] Nitrogen;
[0180] Carbon dioxide-based monomer: propylene carbonate, boiling point 242℃;
[0181] Antioxidant: A complex system composed of antioxidants 1010 and 168, manufactured by BASF under the brand name B215 (composed of 33 wt% Irganox). (A mixture of 1010 and 67wt% Irgafos 168).
[0182] Catalyst a: A mixture of lithium acetylacetonate and potassium carbonate in a weight ratio of 1:1;
[0183] (2) Preparation of amino-terminated polyamide prepolymers
[0184] Caprolactam, diamine, and deionized water were mixed and then subjected to a polymerization reaction. The polymerization reaction was carried out at a pressure of 0.6 MPa, a temperature of 250 °C, and a time of 5 h. The molar ratio of caprolactam to diamine was 40:1, and the amount of deionized water added was 3% of the mass of caprolactam.
[0185] After the polymerization reaction is completed, the reaction system is depressurized to 1 standard atmosphere at a rate of 0.01 MPa / min. The reaction product is then extruded under nitrogen protection, quenched in a 25°C cold water bath and pelletized. Then it is placed in a vacuum oven at 100 Pa and 50°C for 8 hours to dry, thus obtaining the double-terminated amino polyamide prepolymer.
[0186] The number-average molecular weight of the amino-terminated polyamide prepolymer is 4950 g / mol;
[0187] (3) Pre-condensation reaction
[0188] After mixing carbon dioxide-based monomers, antioxidants, catalyst a and all the double-terminated amino polyamide prepolymers obtained in step (2), a pre-condensation reaction was carried out. During the reaction, reflux was carried out and the column top temperature of the condensation system was controlled to be 220°C, which is lower than the boiling point of the carbon dioxide-based monomer.
[0189] The pre-condensation reaction was carried out at a pressure of 1 standard atmosphere, a temperature of 230℃, and a time of 2 hours.
[0190] The molar amount of carbon dioxide-based monomer added is twice the molar amount of diamine added to prepare the amino-terminated polyamide prepolymer;
[0191] The mass of catalyst a added is 400 ppm of the mass of the amino-terminated polyamide prepolymer;
[0192] The amount of antioxidant added is 500 ppm of the mass of the double-terminated amino polyamide prepolymer;
[0193] (4) Final condensation reaction
[0194] After the pre-polymerization reaction was completed, the reaction system was subjected to a final polymerization reaction. The pressure of the final polymerization reaction was 100 Pa, the temperature was 270 °C, and the time was 5 h.
[0195] After the final polycondensation reaction is completed, the system is restored to 1 standard atmosphere, and the reaction product is squeezed out from the bottom valve of the reactor under nitrogen protection. After being cooled in a water bath at 25°C, stretched into strips, and granulated, it is placed in a vacuum oven at 100 Pa and 80°C for 24 hours to dry, thus obtaining carbon dioxide-based polyamide with a number average molecular weight of 32800 g / mol, a molecular weight distribution index of 1.6, and a melting point of 218°C.
[0196] like Figure 6 As shown, peaks 1 and 2 in the Fourier transform infrared spectrum of the carbon dioxide-based polyamide represent the coupling of the NH stretching vibration and NH bending vibration with the CN stretching vibration in the urethane and amide bonds, respectively; peaks 3 and 4 represent the asymmetric and symmetric stretching vibrations of -CH2-, respectively; peak 5 represents the C=O stretching vibration in the urethane and amide bonds; and peak 6 represents the NH bending vibration. Compared to the free -NH and -C=O stretching vibrations, the stretching vibration peaks of these two chemical bonds in the carbon dioxide-based polyamide show a significant red shift, which is due to the formation of numerous hydrogen bonds between the functional groups in the carbon dioxide-based polyamide.
[0197] An application of carbon dioxide-based polyamide is described, in which the carbon dioxide-based polyamide prepared in this embodiment is used to prepare fibers. The specific steps are as follows: the carbon dioxide-based polyamide is melt-extruded at 275°C, and then passed through a spinneret (orifice diameter 0.25 mm, spinneret draw ratio 40) at a pressure of 10 MPa by a metering pump. It enters a 20°C tunnel and is cooled and solidified by cooling air at a speed of 0.6 m / s and a relative humidity of 65%. After being oiled (oiling rate 1.0%), it is hot-stretched on a hot roller at a temperature of 140°C with a total draw ratio of 4.5 times to achieve a high axial orientation of the macromolecular chains.
[0198] The resulting fiber has a specification of 1.63 dtex × 38 mm and a breaking strength of 5.8 cN, meeting the requirements of conventional clothing fabrics, industrial textiles and other fields.
Claims
1. A method for preparing carbon dioxide-based polyamide, characterized in that, A polycondensation reaction is carried out after mixing a double-terminated amino polyamide prepolymer, a carbon dioxide-based monomer, and a reaction aid to obtain a carbon dioxide-based polyamide. The reaction aids include catalyst a, which is lithium acetylacetonate and / or carbonate; Polycondensation reaction is divided into a pre-polymerization reaction stage and a final polymerization reaction stage. In the pre-polymerization reaction stage, condensation reflux is carried out during the reaction process, and the column top temperature of the condensation system is controlled to be lower than the boiling point of the carbon dioxide-based monomer.
2. The method for preparing a carbon dioxide-based polyamide according to claim 1, characterized in that, The number average molecular weight of the amino-terminated polyamide prepolymer is 1000-5000 g / mol.
3. The method for preparing a carbon dioxide-based polyamide according to claim 2, characterized in that, The preparation process of the double-amino-terminated polyamide prepolymer is as follows: a polymer reaction is carried out by mixing lactam, diamine and deionized water, or a polymer reaction is carried out by mixing amino acid, diamine and catalyst b, to obtain the double-amino-terminated polyamide prepolymer; wherein, catalyst b is lithium acetylacetone and / or carbonate; the polymerization reaction pressure is 0.2-0.6 MPa, the temperature is 200-250℃, and the time is 2-5 h.
4. The method for preparing a carbon dioxide-based polyamide according to claim 3, characterized in that, The lactam is caprolactam or decanolactam, the amino acid is 11-aminoundecanoic acid, and the diamine is one or more of C4-C10 diamines; the molar ratio of lactam or amino acid to diamine is 6-40:1, the mass of deionized water added is 2-3% of the mass of lactam added, and the mass of catalyst b added is 100-800 ppm of the mass of amino acid added.
5. The method for preparing a carbon dioxide-based polyamide according to claim 1, characterized in that, The carbon dioxide-based monomer is one or more of dimethyl carbonate, diethyl carbonate, ethylene carbonate, propylene carbonate, and methyl ethyl carbonate; the molar amount of the carbon dioxide-based monomer is 1.1-2 times the molar amount of the diamine used to prepare the double-terminated amino polyamide prepolymer.
6. The method for preparing a carbon dioxide-based polyamide according to claim 1, characterized in that, The carbonate is potassium carbonate or sodium carbonate; the mass of catalyst a added is 100-400 ppm of the mass of the amino-terminated polyamide prepolymer.
7. The method for preparing a carbon dioxide-based polyamide according to claim 1, characterized in that, The pressure during the pre-condensation reaction stage is one standard atmosphere, the temperature is 200-230℃, and the time is 1-2 hours.
8. The method for preparing a carbon dioxide-based polyamide according to claim 1, characterized in that, The pressure during the final polycondensation reaction stage is 100-300 Pa, the temperature is 240-270 °C, and the time is 3-5 h.
9. A carbon dioxide-based polyamide, characterized in that, The carbon dioxide-based polyamide was prepared by any one of the preparation methods described in claims 1 to 8; the number average molecular weight of the carbon dioxide-based polyamide was 18,000-33,000 g / mol, the molecular weight distribution index was 1.5-3.0, and the melting point was 170-220℃.
10. The application of a carbon dioxide-based polyamide in the preparation of fibers, films, or plastic products, characterized in that, The carbon dioxide-based polyamide is the carbon dioxide-based polyamide as described in claim 9.
Citation Information
Patent Citations
Preparation method of carbon-dioxide-base polyurea high polymer material
CN104650322A
Silicate / isocyanate composite elastomer and preparation method thereof
CN113105600A
Self-repairable siloxane modified polyurethane material and preparation method thereof
CN114891180A
Method for preparing polyester through copolymerization of carbon dioxide and epoxide
CN116410455A
Method for synthesizing branched polyester by using polyester and carbon dioxide derivative and product thereof
CN119613683A